2010
DOI: 10.4193/rhin08.223
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in severe nasal polyposis - a possible beneficial effect? A report of three cases

Abstract: This is the first report describing the successful treatment of severe nasal polyposis with chemotherapy. Based on this experience, we suggest a phase II trial with chemotherapy, preferably "low dose" methotrexate, in patients with severe nasal polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In 1996, Comet et al 97 showed that low-dose methotrexate (10 mg once weekly ϫ1 year) was an effective steroid-sparing agent. Two other promising reports (Asplund et al 98 and Buyukozturk et al 99 ) showed dramatic improvement of nasal polyposis in patients treated with low-dose methotrexate.…”
Section: Chemotherapy and Nasal Polyposismentioning
confidence: 92%
See 1 more Smart Citation
“…In 1996, Comet et al 97 showed that low-dose methotrexate (10 mg once weekly ϫ1 year) was an effective steroid-sparing agent. Two other promising reports (Asplund et al 98 and Buyukozturk et al 99 ) showed dramatic improvement of nasal polyposis in patients treated with low-dose methotrexate.…”
Section: Chemotherapy and Nasal Polyposismentioning
confidence: 92%
“…Two other promising reports (Asplund et al . 98 and Buyukozturk et al . 99 ) showed dramatic improvement of nasal polyposis in patients treated with low-dose methotrexate.…”
Section: Treatmentmentioning
confidence: 95%
“…The weekly dose of MTX 10 mg was chosen based on two anecdotal reports 16,17 and considering its well-known safe and low-dose (7.5-30 mg/week) prescription in standard indications. 24 Gastrointestinal disturbances and a slight deterioration in liver function were the two most commonly observed adverse effects with 8.8 mg/week (4.6-18 mg) of MTX for an average of 36.5 weeks (27-132 weeks).…”
Section: Eligibilitymentioning
confidence: 99%
“…Two previous case reports have documented the regression of nasal polyps in patients who were treated with MTX for asthma and malignancy and coincidentally presented with nasal polyposis. 16,17 Inhibition of dihydrofolate reductase and T-lymphocyte proliferation and triggering T-lymphocyte apoptosis are among the autoinflammatory mechanisms of MTX. 18 Because T helper 1, 2, and 17 cells play roles in the three different types of CRSwNP, 1 MTX can be a promising treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…Many adjunctive agents have been utilized to control CRS including antimycotics,9598 anti-IgE,99 anti-IL5,100,101 antihistamine,102,103 aspirin desensitization,104 bacterial lysates,105108 capsaicin,109 complementary and alternative medicine,3,110–114 decongestants,115 furosemide,116 immunosuppressants,117,118 leukotriene antagonists,119,120 nasal irrigation,121127 mucolytic agents,128 phototherapy,129 probiotics,130 and proton pump inhibitors (PPIs) 131. There was limited evidence on the effect of these options.…”
Section: Other Emerging Optionsmentioning
confidence: 99%